Factors influencing the development and implementation of advanced radiographer practice in Australia – a qualitative study using an interpretative phenomenological approach. Issue 3 (16th July 2014) - Page, Barbara A.; Bernoth, Maree; Davidson, Rob
Abstract Introduction The purpose of this study was to explore the factors influencing the implementation or the lack of implementation of advanced practitioner role in Australia. Methods This study uses an interpretative phenomenological approach to explore the in‐depth real life issues, which surround the advanced practitioner as a solution to radiologist workforce shortages in Australia. Research participants are radiographers, radiation therapists and health managers registered with the Australian Institute of Radiography (AIR) and holding senior professional and AIR Board positions with knowledge of current advanced practice. Results In total, seven interviews were conducted revealing education, governance, technical, people issues, change management, government, costs and timing as critical factors influencing advanced practice in Australia. Conclusions Seven participants in this study perceived an advanced practice role might have major benefits and a positive impact on the immediate and long‐term management of patients. Another finding is the greater respect and appreciation of each other's roles and expertise within the multidisciplinary healthcare team. Engagement is required of the critical stakeholders that have been identified as 'blockers' (radiologists, health departments) as well as identified allies (e.g. emergency clinicians, supportive radiologists, patient advocacy groups). The research supports that the AIR has a role to play for the professional identity of radiographers and shaping the advanced practice role in Australia.